Analisis Potensi Pariwisata di Desa Sambirata Kecamatan Cilongok Kabupaten Banyumas Berbasis Mitigasi Bencana - Ni`maturrohmah Ni`maturrohmah; Suwarsito Suwarsito; Esti Sarjanti (Proceedings Series on Social Sciences & Humanities, 2022)
Tourism is an important sector in the construction and development of an area. Tourism can increase local government revenue and income for each tourism object. Sambirata Village located in Cilongok District, Banyumas Regency has 3 natural tourism potentials, namely Telaga Kumpe, Curug Cipendok, Bukit Gondang. Seeing the tourism potential of Sambirata Village, an assessment is needed for the development of these tourist objects. In addition, by looking at the assessment, it can also be known the level of disaster mitigation that exists. The purpose of this study is to determine the classification of tourism potential of each tourist attraction in Sambirata Village and also to find out the level of disaster security of each tourist attraction. Data collection using GPS tools, GIS Software, Google Maps, and cameras combined with direct observation and classification of tourism potential assessments according [3]guidelines that have been modified. The results of this study are (1) Telaga Kumpe, and Curug Cipendok are among the tourist attractions that have a high classification of tourism potential, while for Bukit Gondang has a low classification of tourism potential. (2) The level of disaster mitigation is in accordance with the high classification of tourism potential of existing tourism objects.